2017
DOI: 10.3233/jad-161130
|View full text |Cite
|
Sign up to set email alerts
|

Palmitate Increases β-site AβPP-Cleavage Enzyme 1 Activity and Amyloid-β Genesis by Evoking Endoplasmic Reticulum Stress and Subsequent C/EBP Homologous Protein Activation

Abstract: Epidemiological studies implicate diets rich in saturated free fatty acids (sFFA) as a potential risk factor for developing Alzheimer’s disease (AD). In particular, high plasma levels of the sFFA palmitic acid (palmitate) were shown to inversely correlate with cognitive function. However, the cellular mechanisms by which sFFA may increase the risk for AD are not well known. Endoplasmic reticulum (ER) stress has emerged as one of the signaling pathways initiating and fostering the neurodegenerative changes in A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 111 publications
1
37
0
Order By: Relevance
“…Knocking-down CHOP expression in SH-SY5Y-APP Swe cells significantly attenuates the palmitate-induced increase in BACE1 expression and Ab genesis (Marwarha et al 2017e). Furthermore, Chop À/À mice fed a palmitate-enriched diet do not exhibit the same increase in BACE1 expression and Ab burden compared to the C57BL/6J wild-type mice fed a palmitate-enriched diet (Marwarha et al 2017e). However, questions still abounded with regard to the molecular mechanism(s) by which CHOP may induce the aforementioned effects.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Knocking-down CHOP expression in SH-SY5Y-APP Swe cells significantly attenuates the palmitate-induced increase in BACE1 expression and Ab genesis (Marwarha et al 2017e). Furthermore, Chop À/À mice fed a palmitate-enriched diet do not exhibit the same increase in BACE1 expression and Ab burden compared to the C57BL/6J wild-type mice fed a palmitate-enriched diet (Marwarha et al 2017e). However, questions still abounded with regard to the molecular mechanism(s) by which CHOP may induce the aforementioned effects.…”
Section: Resultsmentioning
confidence: 99%
“…NF-jB activation and transcriptional activity is required for the palmitate-induced CHOP-mediated increase in BACE1 expression and subsequent engenderment of Ab We determined the effects of palmitate treatment on NF-jB activation in SH-SY5Y-APP Swe human neuroblastoma cells (cells that stably express the Swedish KM670/671NL double mutant AbPP) as well as the effects of palmitateenriched diet on NF-jB activation in the mouse hippocampus. Our recent study showed that exogenous palmitate treatment, for 24 h at 100 lM terminal concentration, increases BACE1 expression in cultured SH-SY5Y-APP Swe cells (Marwarha et al 2017e). We therefore used this experimental paradigm, exogenous palmitate at 100 lM terminal concentration in the cell culture medium for 24 h, throughout this study.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, it is well known that BACE1 is a stress-induced protease whose activity has been shown to increase in many types of stress conditions. Furthermore, both in vitro and in vivo experiments revealed that activated caspase-3-dependent apoptosis resulted in an increase in BACE1 levels (34)(35)(36). Because BAP31 is related to ER quality control, the markers Figure 6.…”
Section: Discussionmentioning
confidence: 99%